2017
DOI: 10.1016/j.jconrel.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Drug-free macromolecular therapeutics: Impact of structure on induction of apoptosis in Raji B cells

Abstract: Recently, we developed a new paradigm in macromolecular therapeutics that avoids the use of low molecular weight drugs. The activity of the “drug-free macromolecular therapeutics” is based on the biorecognition of complementary motifs at cell surface resulting in receptor crosslinking and apoptosis induction. The system is composed of two nanoconjugates: (1) a single-stranded morpholino oligonucleotide (MORF1) attached to an anti-CD20 Fab′ fragment (Fab′-MORF1); (2) multiple copies of complementary oligonucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 67 publications
(99 reference statements)
2
26
0
Order By: Relevance
“…As the internalization is an indicator for the CD20 crosslinking, this result demonstrated that the multiple binding of P‐(MORF2) 10 to Fab′‐MORF1 that was bound to CD20 facilitated the CD 20 crosslinking, which eventually resulted in elevated level of apoptosis. These data are in agreement with our previous study that demonstrated that the higher the valence of the P‐(MORF2) x conjugate the higher the apoptotic response, due to the enhanced biorecognition.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As the internalization is an indicator for the CD20 crosslinking, this result demonstrated that the multiple binding of P‐(MORF2) 10 to Fab′‐MORF1 that was bound to CD20 facilitated the CD 20 crosslinking, which eventually resulted in elevated level of apoptosis. These data are in agreement with our previous study that demonstrated that the higher the valence of the P‐(MORF2) x conjugate the higher the apoptotic response, due to the enhanced biorecognition.…”
Section: Resultssupporting
confidence: 93%
“…2.5 × 10 5 Raji cells were treated with cell culture medium (control) or consecutive treatment Fab′‐MORF1 (1 × 10 −6 m , 1 h)/P‐(MORF2) x (1 × 10 −6 m , 24 h). Then cells were washed by PBS and stained with Annexin V‐FITC and PI in dark for 15 min, followed by flow cytometry analysis . All experiments were carried out in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously we have demonstrated the higher the valence, the more efficient and pronounced are CD20 cross-linking and apoptosis induction. 24 We also anticipate once several closely related apoptosis signals are high enough in magnitude, then the intracellular RTX resistance due to abnormal modulation ( e.g ., downregulation of Bax and Bak) 25 might be compensated. Thus, potentially, the two-step CD20 cross-linking amplifiers are engaged in a two-pronged effort to combat RTX resistance: circumventing Fc-related resistance pathways and confronting abnormal modulations with enhanced apoptosis, in a way that is independent of immune effector functions.…”
mentioning
confidence: 99%